Dimensi Kompetensi Manajerial Kepala Sekolah Smp Negeri 01 Dan Smp Negeri 03 Kubu Kabupaten Rokan Hilir - Ahmad Daud (LPPM STAI Diniyah Pekanbaru, 2019)
The purpose of this research is to describe the implementation of Managerial Competence and Periodization of The Headmasters of SMPN 01 dan SMPN 03 Kubu Kabupaten Rokan Hilir. It is qualitative research with a case study. The results of the research are as follows: (1) The implementation of managerial competence of the headmasters of SMPN 01 and SMPN 03 has not been implemented well yet suited to the indicator of managerial standard competence. (2) The factors inhibiting the implementation of managerial competence in SMPN 01 and SMPN 03 are as follows: (a) The location of the schools is far from the city which inhibits the school programs. (b) The lack of means and infrastructures to support the teaching and learning processes at schools. (c) The lack of motivation by the headmasters. The headmasters had been in charge for 3 periodic years without any periodization of the position, (d) The headmasters do not have a standard competence of headmaster according to the government regulation. (e) The lack of coordination and cooperation between the headmasters and their subordinates. (3) The factors affecting the periodization of headmaster position: (a) The request from the public figure in the school environment to the Head of UPTD, since the headmaster is one of the figures needed by the society. (b) There is a worry from UPTD that a new headmaster will not be able to adapt to the environment of the society. (c) There is a worry from UPTD for the social impact that arises in the society if the headmaster is replaced.